Addressing risk management difficulties in children with food allergies. Issue 4 (15th February 2021) - Eigenmann, Philippe A.; Ebisawa, Motohiro; Greenhawt, Matthew; Hourihane, Jonathan O'B; Perry, Tamara T.; Remington, Benjamin C.; Wood, Robert A.
Abstract: Risk is a concept inherent in every medical procedure. It can be defined as the probability of an adverse event in a defined population over a specified period of time. In the frame of food allergy management, it might be related to a diagnostic procedure, a treatment, or the consumption of foods. The risk of an adverse event can also be augmented by individual factors. This rostrum article discusses various aspects faced by children with food allergies in the light of risk, and their practical implications. Identifying personal risks for severe reaction, such as unstable asthma, and correcting them whenever possible also contribute to a reduction of the risk inherent to food allergy. Among the facets discussed, oral food challenges (OFC) are the most common diagnostic procedures implying an inherent risk. The risk of OFCs can be minimized by correct indication and timing of the test, a safe setting, as well as by ensuring that the patient is otherwise well without potential stressor potentially increasing the risk of a more severe reaction. Oral immunotherapy (OIT) has been studied as a potential treatment for increasing the threshold dose for reaction, and thus reducing the risk of accidental reaction. Nevertheless, the procedure is not devoid of risk as the patients may and do often react during the course of the procedure. Ingestion of trace amounts in processed foods, mainly in community settings such as restaurants, schools, or day care, represents a potential risk of reactions, although for a minority of patients. Precautionary allergen labeling (PAL) is a widespread strategy to reduce the potential risk of reactions due to traces. However, PAL is currently inefficient due to inconsistent labeling, also not indicating a clear maximum amount possibly present in the manufactured food. Finally, cost‐effectiveness needs to be considered in risk management, as many risk reduction procedures are clearly not cost‐effective.